PENINGKATAN PENGUASAAN KOSAKATA BAHASA INGGRIS MELALUI METODE BERMAIN KARTU BERGAMBAR TK BILINGUAL PONTIANAK TENGGARA - Yulita Yulita; Marmawi Marmawi; Halida Halida (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2017)
AbstractThis study aims to see the improved mastery of english vocabulary through methods of playing bilingual kindergarten picture card pontianak southeast. Based on the results of research and data analysis can be concluded: (1) Learning planning in improving vocabulary mastery The English language of children aged 5-6 years can be categorized as "excellent", with indicators have made a good daily activity plan, selection of materials, selection of learning methods, problem formulation. (2) Implementation of learning in the mastery of English language vocabulary of children aged 5-6 years can be categorized as "excellent", among others: determine the material and formulate goals, manage class interaction, demonstrate the ability in learning, carry out assessment process and learning outcomes, general impression process learning outcomes.(3) The result of the improvement of vocabulary mastery of English language is categorized very well, because every indicator has improved with very good category. Suggestions that can be given in this research are expected to be the method of playing picture card can be one way to improve the mastery of English language vocabulary of children aged 5-6 years.Keywords: Mastery of English Vocabulary, Picture Card Playing Method.